Health and Environmental Risks Due to the Use of Mercury-Containing Lamps - Ayme Huertas, Ivan Alexander (2020)
This research was developed in order to analyze the management and management of mercury-containing lamps and to identify the health and environmental risks related to their mercury content. Taking into account that mercury is a natural and toxic substance, which once released into the environment it can remain and circulate in air, water and soil. It also causes a wide range of systematic effects in humans (kidneys, stomach, lungs and nervous system). In Peru, the lamps are considered as waste of electrical and electronic equipment (WEEE) at the end of their useful life. The environmental problem they present is their mercury content, is not essential for any metabolic process and is bioaccumulable in living beings. Taking into account the risk it represents, many countries of the world, including Peru, signed the Minamata Agreement, and have been implementing national planning and management instruments to implement a correct waste management of the mercury. As part of this commitment, Peru has been drafting the National Plan for the Application of the Minamata Convention on Mercury, which aims to specify actions to protect human health and the environment from anthropogenic emissions and releases of mercury and mercury compounds. It concludes that lamps, at the end of their useful life, constitute a hazard due to their mercury it contains; a proper management is an important factor to reduce the risks to human health and the environment.